Designing a Novel High Performance Four-to-Two Compressor Cell Based on CNTFET Technology for Low Voltages - Mehdi Bagherizadeh; Mona Moradi; Mostafa Torabi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Compressor cell is often placed in critical path of multiplier circuits to perform partial product summation. Therefore it plays a significant role in determining the entire performance of multiplier and digital system. Respecting to the necessity of low power design for portable electronic, designing a low power and high performance compressors seems to be a good solution to overcome of these problems for computations. In this paper a novel high performance four-to-two compressor cell is proposed using Carbon Nanotube Field Effect Transistors (CNTFETs) technology. The new cell is based on Majority Function, NOR, and NAND gates. The main advantage of proposed design in comparison with former cells is the ease of obtaining CARRY output by means of Majority function. Simulations have been done with 32nm technology node using Synopsys HSPICE software. Simulation results confirm the priority of the proposed cell compared to other state-of-the-art four-to-two compressor cells.